Fabrication of novel carboxyl and amidoxime groups modified luffa fiber for highly efficient removal of uranium(VI) from uranium mine water. Issue 4 (August 2021) - Xiao, Feng; Cheng, Yanxia; Zhou, Pengcheng; Chen, Shouxian; Wang, Xuejiao; He, Ping; Nie, Xiaoqin; Dong, Faqin
Abstract: Novel luffa cylindrica adsorbent modified with carboxyl and amidoxime groups is successfully prepared by a simple water bath method for effective U(VI) uptake from uranium-containing wastewater and real uranium mine water. The critical factors affecting U(VI) adsorption are explored, such as grafting time of carboxyl and amidoxime groups, solution pH, initial concentration of U(VI) and contact time. The results show that LC-CA2 -AO4 obtained under optimal condition possesses outstanding adsorption performance to U(VI) ( q max, 399.1 mg g −1 ). Repeated adsorption/desorption experiments display that LC-CA2 -AO4 can be efficiently regenerated by 0.50 mol L −1 HCl solution and reused for uranium adsorption. Adsorption capacity and desorption efficiency of LC-CA2 -AO4 to U(VI) drop slightly after eight cycles of regeneration test. The accordance of kinetic data with pseudo-second-order kinetics model suggests that the adsorption reaction is controlled by chemical process. Moreover, LC-CA2 -AO4 displays high removal rate to U(VI) in real uranium mine water. Based on this work, it is demonstrated that LC-CA2 -AO4 would be a promising candidate for potential application in field of uranium adsorption. Graphical Abstract: ga1 Highlights: Bifunctional luffa-based fiber has been prepared by water bath heating method. As-prepared fibers possess excellent adsorption capacity to U(VI). As-prepared fibers exhibit satisfactory reusability for U(VI) extraction. As-prepared fibers are employed to adsorb U(VI) in real uranium mine water.